First retrospective studies with etiological confirmation of porcine transmissible gastroenteritis virus infection in Argentina - Piñeyro Piñeiro, Pablo Enrique (2018)
Background: (TGEV) was made by the NationalServices of Animal Health of Argentina (SENASA) to the World Organization of Animal Health (OIE). The notificationwas based on a serological diagnosis in a small farm with a morbidity rate of 2.3% without enteric clinical signs. Inorder to determine if TGEV was circulating before the official report, a retrospective study on cases of neonataldiarrhea was performed. The selection criteria was a sudden increase in mortality in 1- to 21-day-old piglets withwatery diarrhea that did not respond to antibiotics. Based on these criteria, three clinical cases were identifiedduring 2010?2015.Results: All animals that were evaluated presented histological lesions consistent with enteric viral infection. Thefeces and ultrathin sections of intestine that were evaluated by electron microscopy confirmed the presence ofround particles of approximately 80 nm in size and characterized by finely granular electrodense nucleoidsconsistent with complete particles of coronavirus. The presence of the TGEV antigen was confirmed by monoclonalspecific immunohistochemistry, and final confirmation of a metabolically-active virus was performed by in situhybridization to detect a TGE mRNA encoding spike protein. All sections evaluated in this case were negative forPEDV and rotavirus A.Conclusions: This is the first case series describing neonatal mortality with etiological confirmation of TGEV inArgentina. The clinical diagnosis of TGEV infections in endemic regions is challenging due to the epidemiologicaldistribution and coinfection with other enteric pathogens that mask the clinical presentation.